La gouvernance du Mobility as a Service (MaaS) : quelle approche de gouvernance favorisent les autorités publiques dans le développement de MaaS ? - Julia JANKE (Tic & Société)
This article aims to highlight the role of public authorities and their governance approach in the development of MaaS (Mobility as a Service) - multimodal mobility platforms. A scientific literature review provides insights into four governance approaches: governing by authority, governing by enabling, governing by doing and a laissez-faire approach. The results reveal that governance approaches by public authorities depend on the regulatory framework defining their competences and capacities to intervene. Public engagement varies according to administrative hierarchy as well as between countries. The resale of public transportation tickets, the selection of mobility services included in the MaaS and geographic service coverage create diverging positions among actors and question the promising goals associated with MaaS development.